LANGUAGE IN ACTION: INTERPRETING ILLOCUTIONARY SPEECH ACTS IN TICK, TICK…BOOM! - Sutrisno, Bejo; Rahim, Dinda Cheril Julian (Sanata Dharma University, 2025)
Although illocutionary speech acts have been extensively studied in everyday and institutional discourse, their application in cinematic narratives remains underexplored. Existing pragmatic research on film dialogue has primarily focused on genre conventions or general speech act patterns, leaving a gap in understanding how illocutionary force constructs character identity and emotional conflict in creative storytelling. This study investigates the illocutionary acts employed by Jonathan Larson, the protagonist in Tick, Tick… Boom!, a Netflix original musical that dramatizes the tension between personal ambition and existential anxiety. Drawing on Searle’s taxonomy, the research adopts a qualitative approach to analyze 76 representative utterances from the film script and scenes, identifying and categorizing illocutionary force. The results reveal four types of illocutionary acts: directives (42.5%), assertives (26.7%), expressives (22.3%), and commissives (6.6%), with directives as the most dominant. These findings suggest that Larson’s linguistic behavior is driven largely by attempts to influence, persuade, and seek validation from others. By situating speech act theory within cinematic pragmatics, this study contributes to a growing body of interdisciplinary research and offers insights for scholars examining language use in media narratives. Future research may consider integrating locutionary and perlocutionary dimensions for a fuller account.